The lure of the Moonflower : a Pink Carnation novel - Willig, Lauren (Willig, Lauren. Pink carnation series., 2015)
"All of Portugal believes that the royal family departed for Brazil just before the French troops marched into Lisbon. Only the English government knows that mad seventy-three-year-old Queen Maria was spirited away by a group of loyalists determined to rally a resistance. But as the French garrison scours the countryside, it's only a matte of time before she's found and taken. It's up to Jane to find her first and ensure her safety. But she has no knowledge of Portugal or its language. Though she is loath to admit it, she needs the Moonflower- an agent with a reputation for brilliance, a tendency toward insubordination, and a history of going rogue."